Masalah Disintegrasi Bangsa - I Ketut Astawa; Alya Rafeyfa Asyla; Amanda Putri; Caecillia Claudia Agatha; Damar Nurcahyo; Isnaini Julianti; Srimurti Eka Octaviani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
National disintegration is a phenomenon of a country's division into separate parts due to various factors that threaten the integrity and unity of the nation. This phenomenon often arises as a response to the dissatisfaction of certain groups, such as attempts to secede by regions or communities that feel marginalized from the development and government process. In addition, socio-political problems such as injustice, corruption, and weak leadership also worsen the condition, eroding the solidity of a unitary state. The impact of national disintegration is not only limited to political and economic aspects, but also extends to social and cultural aspects. National identity can be eroded, relations between citizens deteriorate, and the sense of solidarity and togetherness fades. Concretely, disintegration can trigger open conflict, destruction of infrastructure, an increase in the number of internally displaced people, and the loss of national stability and cohesion. Therefore, efforts to prevent disintegration through strengthening unity, equitable development, and conflict management are very important.